Utilization of flashmx for making educational android games - Supriyadi, Supriyadi (Jurnal Mandiri IT, 2024)
Technology that is increasingly developing has a positive impact on society, especially during a pandemic, in the world of smartphones there are many entertainment media that people can choose to enjoy, one of which is games. Game is currently a popular media, with this the author wants to make a game called crashing into a tree made using Adobe FlashMX software. This game is made for the Android platform. In making it, explained the game design and script used in the game. The methodology used is GDLC (Game Development Life Cycle) which is a game development process that applies an iterative approach. This game has features like game levels and high scores to save scores to database. This tree hitting game is of the 2D type, because it was made using Adobe FlashMX software with the Action Script programming language. The expected output from its creation is the design of a fallen tree game application in the form of a 2-dimensional image, which can be used by all groups ranging from children to adults with the aim of providing entertainment to people who are feeling bored or bored and can fill their time by playing this game.